1997
DOI: 10.1007/bf01739642
|View full text |Cite
|
Sign up to set email alerts
|

Retinal function with lens-induced myopia compared with form-deprivation myopia in chicks

Abstract: Retinal function differs in LIM and FDM, as indicated by differences in the oscillatory potentials. This difference may stem from the fact that in FDM the retinal image is continuously defocused, whereas images are ultimately focused on the retina in LIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 17 publications
3
38
0
1
Order By: Relevance
“…We reported earlier that the eyes of chicks elongated to compensate for the effect of minus lenses (up to -16 dpt) in 6 days after the application of the lenses [6]. In this study, we investigated the effect of L-NAME, an inhibitor of nitric oxide synthetase (NOS), on the development of LIM under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported earlier that the eyes of chicks elongated to compensate for the effect of minus lenses (up to -16 dpt) in 6 days after the application of the lenses [6]. In this study, we investigated the effect of L-NAME, an inhibitor of nitric oxide synthetase (NOS), on the development of LIM under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This lens assembly positioned the lenses 5 mm in front of the corneal surface of the chick's eye. The absolute power of the lens was -18.0 dpt [6]. To prevent blurring of vision by the condensation of moisture on the lenses, a coating was sprayed on the inner and outer surfaces of the assembly before it was applied to the eye.…”
Section: Goggle-lens Assembly To Induce Myopiamentioning
confidence: 99%
“…osilatuar potansiyel (OP) amplitüdlerinin uzun aksiyel uzunluk'lu gözlerde zayıflamış olduğunu bulmuş ve fonksiyonel değişikliklerin deprive-form miyopik retinanın iç tabakasından ortaya çıktığını ileri sürmüşlerdir. 15 Son elektrofizyolojik çalışma, yüksek miyopik ço-cuklarda anormal retinal fonksiyon bulguları gö-steren ERG bulguları olmuştur. Araştırmacılar, retinal disfonksiyonun insan emetrop sürecinin tahribi sonucu oluştuğunu ve refraksiyon kusuru gelişimi ile sonuçlanabileceğini öne sürmüşlerdir.…”
Section: Discussionunclassified
“…It has been reported that myopia induced by negative lenses produced axial-length elongation and refractiveerror changes that were dependent on the lens power [11,35] . Irving et al [33,40] reported that positive and negative lenses ranging in power from -20 to +30 D induced myopia and hyperopia in hatching chicks, but these lenses did not change the lens thickness between control and treated eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Negative lens-induced chick myopia models with axial-length elongation have been widely used to investigate the mechanism of myopia progression [35] and also to evaluate the effects of drugs such as atropine [36] and pirenzepine [37] , which prevent myopic progression and axial-length growth in children [38,39] . Therefore, we used the negative lens (-8 D)-induced myopia model in chicks to evaluate the efficacy of BC extract in preventing myopia-related changes.…”
Section: Discussionmentioning
confidence: 99%